Language Barriers and Cultural Differences Faced by Thai Students in Learning Experiences at STAIN Jembe - Ninuk Indrayani (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2015)
The issue of language barriers is crucial in social interactions and cultural differences among foreign students. With language and cultural challenges, they must strive harder to achieve their academic goals. This research focuses on the phenomenon of Thai students studying in the Islamic Education (PAI) program, Tarbiyah Department at STAIN Jember. Using a qualitative approach, the study aims to identify the problems faced by these students in their learning experiences at STAIN Jember and the solutions they undertake. Permasalahan tentang kendala bahasa menjadi penting dalam pergaulan dan perbedaan budaya di antara mahasiswa asing. Dengan permasalahan bahasa dan budaya, mereka harus berjuang untuk mendapatkan ilmu yang ingin mereka raih dengan upaya yang lebih sulit. Penelitian ini fokus pada fenomena adanya mahasiswa Thailand yang sedang menuntut ilmu dalam prodi PAI jurusan Tarbiyah STAIN Jember. Dengan pendekatan kualitatif, penelitian ini berusaha mengidentifikasi permasalahan yang dialami oleh mahasiswa tersebut dalam pengalaman belajarnya di STAIN Jember dan upaya solusi yang mereka lakukan.